"Development of the creative potential of children in the system of vocational training of future teachers - Kharkіvska A. (Problems of Engineer-Pedagogical Education, 2023)
The article highlights the problem of developing the creative potential of children during the training of future teachers. An important stage in the development of the creative potential of the child's personality is the quality of vocational training of future teachers in higher education institutions, which in the future will ensure the timely detection and successful development of children's creative potential. The concept of "potential" is defined as a set of hidden abilities, opportunities that can be used for the implementation of specific activities. It was found that human potential is most often manifested in creative activities and involves the disclosure of the creative potential of the individual. The author analyzes the scientific and pedagogical literature on the definition of such concepts as "creativity", "abilities", "talents", and "creative potential". The most thorough interpretations that correspond to the topic and purpose of the study are highlighted in the article. Creativity is defined by the author as a process that involves the realization of abilities, including creative abilities, to solve problems and involves the practical application of acquired knowledge to create new cultural objects. Endowments, as natural human resources, are prerequisites for the formation and development of abilities that improve throughout life. The author defined that creative potential is a set of skills and abilities, as well as personal qualities that in the process of creative activity contribute to self-affirmation, self-realization and self-development of the individual. It was found that the creative potential of children develops primarily during education, so special attention needs to be paid to the training of future teachers. The author formed and highlighted the stages of vocational training of future teachers for the development of children's creative abilities, including the identification of creative abilities, the process of developing creative abilities, and control over individual development of creative potential and pedagogical practice. Emphasis is placed on the need for future teachers to master different ways of developing the creative potential of children, including children with special educational needs: problemsolving and research tasks, participation in competitions and contests, individual creative work etc. Development of children's creative potential in the system of vocational training of future teachers is a purposeful educational process aimed at mastering professional and special knowledge and skills, special methods and technologies necessary for future activities to identify and develop creative potential of children, including children with special educational needs.